1997
DOI: 10.1016/s1388-3437(97)80065-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient simulation of network performance by importance sampling

Abstract: Simulation model Parallel and distributed simulation Hybrid techniques Rare event provoking Variance reduction Figure 1.2 : An overview of speed-up simulation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The idea of adaptive biasing was introduced in [Heegaard 1997] for multiclass, homogeneous demand networks, where an arriving call requires the same number of units among the resource types in its demand set. In Heegaard [1998], this method was applied to nonhomogeneous demands, and calls with different priorities.…”
Section: Adaptive Issc Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of adaptive biasing was introduced in [Heegaard 1997] for multiclass, homogeneous demand networks, where an arriving call requires the same number of units among the resource types in its demand set. In Heegaard [1998], this method was applied to nonhomogeneous demands, and calls with different priorities.…”
Section: Adaptive Issc Methodsmentioning
confidence: 99%
“…In Heegaard [1996], methods were suggested for calculating f N (l ), which are based on a weight for each l that is a product of contribution and likelihood. In Heegaard [1997], a more complex algorithm was suggested. De Boer et al [2005], suggested using cross entropy as the guide to do the sampling.…”
Section: Adaptive Issc Methodsmentioning
confidence: 99%
“…IS is well explained in Glynn and Iglehart [1989], Shahabuddin [1994], Heidelberger [1995], Sadowsky [1996], and the several other references given there. Application of IS to the simulation of communication systems is studied, for example, by Parekh and Walrand [1989], Chang et al [1994;, Bonneau [1996], Falkner et al [1999], and Heegaard [1998]. Chang et al [1994] derived an asymptotically optimal change of measure, based on the theories of effective bandwidth and large deviations, for estimating the probability p that a queue length exceeds a given level x before returning to empty, given that the queue is started from empty, for a single queue with multiple independent arrival sources that satisfy a large deviation principle.…”
Section: Introductionmentioning
confidence: 99%
“…In reliability models for instance, ε may represent a maximum failure rate of a component in the case of dynamic models (Shahabuddin 1994), or the reliability of a component in the case of static models. In queuing performance evaluation models, ε may be chosen as 1/B where B is the buffer size, so that the buffer overflow probability γ → 0 as ε → 0 (Juneja 1993, Heegaard 1998). …”
Section: Properties Of Rare Event Estimatorsmentioning
confidence: 99%
“…In particular, there has been a line of research of the asymptotic behavior of rare event simulation estimators when the rarity of the events goes to 0, which has led to define new concepts such as bounded relative error, asymptotic optimality (both concerning the size of the confidence interval relatively to the considered rare event), and more recently bounded normal approximation (looking at the coverage of the confidence interval). These concepts focus on the precision attained and the robustness of the simulation estimators (both are important features, see for example the discussion in (Heegaard 1998)), but do not take into account the computational times associated with them. We show in this paper that those properties are not defined generally enough to encompass some classes of estimators actually exhibiting a very nice behavior.…”
Section: Introductionmentioning
confidence: 99%